Designing Printable Medicinal Products: Solvent System and Carrier‐Substrate Screening. Issue 8 (9th July 2014) - Raijada, Dhara; Genina, Natalja; Fors, Daniela; Wisaeus, Erik; Peltonen, Jouko; Rantanen, Jukka; Sandler, Niklas; Qu, Haiyan; Rantanen, Jukka; Ulrich, Joachim
Abstract More flexible yet robust manufacturing solutions are needed in the pharmaceutical industry. Tablet compaction is no longer the obvious choice for commercial‐scale processing of innovative drug delivery systems. Engineering solutions have gained wide attention in the pharmaceutical industry. Technical innovations within printing are considerable solutions for future product design. Printable medicinal products of a model compound are designed and an analytical approach for imaging the model compound in the printed medicinal products is investigated. The potential implications of using a unique combination of ink solution and carrier‐substrate for designing a specific crystallization process and future directions towards continuous manufacturing of personalized medicinal products are discussed.